2009
DOI: 10.1002/adma.200900376
|View full text |Cite
|
Sign up to set email alerts
|

Impurity Doping in Silicon Nanowires

Abstract: Silicon nanowires (SiNWs) have considerable potential to assist the realization of next‐generation metal‐oxide semiconductor field‐effect transistors (MOSFETs) with vertical structures. Impurity doping and its control is a key technique in the creation of SiNW devices, which renders it necessary to develop characterization methods for dopant atoms in SiNWs. In this Research News, we described how the states of the dopant atoms boron and phosphorus can be detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
106
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 19 publications
11
106
0
2
Order By: Relevance
“…Various nanowires, such as Si [4], ZnO [5], ZnS [6,7], GaN [8], GaP [9] and SiO x [10] nanowires, have been synthesized by different methods. Among them, SiO x nanowires attract special attention in optoelectronic applications because of their high intense and stable blue light emission at the room temperature [11,12] and their potential applications in the field of light localizations [11,13], low dimensional waveguides [11,13,14], and scanning near-field optical microscopy [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Various nanowires, such as Si [4], ZnO [5], ZnS [6,7], GaN [8], GaP [9] and SiO x [10] nanowires, have been synthesized by different methods. Among them, SiO x nanowires attract special attention in optoelectronic applications because of their high intense and stable blue light emission at the room temperature [11,12] and their potential applications in the field of light localizations [11,13], low dimensional waveguides [11,13,14], and scanning near-field optical microscopy [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The peak position agrees well with the reported values for 11 B-Si (620 cm -1 ) in B-doped bulk silicon 44 and 11 B-Si (618 cm -1 ) in B-doped Si-nanowire. 45 In this study, we used natural boron ( more abundant 11 B-Si peak was detected. Therefore, the reduction of B 2 O 3 in the borosilicate glass, which was suggested by the cyclic voltammetry and potential-pO 2− diagram, is confirmed.…”
Section: H O (In Glass)mentioning
confidence: 99%
“…The electronic properties can be precisely controlled by introducing dopant reactants during the growth. Addition of different ratios of diborane or phosphine to silane reactant during growth produces p-or n-type Si nanowires with effective doping concentrations directly related to the silane: dopant gas ratios (Cui et al, 2000) (Cui et al, 2001) (Zheng et al, 2004) (Fukata, 2009). It was demonstrated that B and P can be used to change the conductivity of Si NWS over many orders of magnitude (Cui et al, 2000).…”
Section: Bottom Up Approachmentioning
confidence: 99%